Níveis e modelos de distribuição de irrigação na cultura da goiabeira nas condições edafoclimáticas do tabuleiros de Russas, Ceará - Maia, Luiz Alberto Freire (2017)
In the state of Ceará, few studies are concerned with irrigation within the cultivation of guava. There is need for studies on irrigation management as a way to determine how to apply water along with determining the best model for the distribution of water in the crop, that is, how to irrigate is a pressing need. Most producers choose the distribution model and then irrigate their crops based only on inaccurate observations, often leading to wrong design decisions along with an excessive application or deficit of water. This study aimed to evaluate the responses within the following parameters: phenological, productive, physical and chemical fruit quality, the cultivation of guava (Psidium guajava L.) variety Paluma under the conditions the semiarid region of Ceará, taking into consideration the use of three irrigation distribution models in combination with five irrigation levels. In the experiment conducted in the Tabuleiros de Russas Irrigation District (DISTAR), Russas, Ceará, split plots and four replications were evaluated under experimental design of randomized complete block. The treatments consisted of the combination of three irrigation distribution methods: micro sprinkler and two distributions of driplines (1 and 2 lines / plant row), which constituted the plots and five irrigation levels (50; 75; 100; 125 and 150% of potential crop evapotranspiration - ETpc calculated), which constituted the subplots. Initially, data were submitted to analysis of variance and data with significant by F test were submitted to regression analysis. Moist soil bulb varied with the flow of the issuers and the diameter was greater in depth of 0.10 m, reaching a maximum of 60 cm profile. The phenological parameters were influenced by irrigation levels with a growth trend with an increase of the blades in cycle 1 and the cycle 2 only for the irrigation system, especially the double drip. The productive characteristics only were influenced by irrigation systems in cycle 2 of culture and higher productivity occurred with drip double and 39.2 ton.ha-1. The quality of Paluma guava fruit were influenced by systems and irrigation levels in different cycles